2012
DOI: 10.1039/c2an35692a
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of a plasmonic thermocycler for the amplification of human androgen receptor DNA

Abstract: A plasmonic heating method for the polymerase chain reaction is demonstrated by the amplification of a section of the human androgen receptor gene. The thermocycler has a simple low-cost design, demonstrates excellent temperature stability and represents the first practical demonstration of plasmonic thermocycling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 32 publications
(39 reference statements)
0
17
0
Order By: Relevance
“…More recently, plasmonics-generated localized heat, a process known as photothermal conversion, has been utilized to speed up the rate of PCR assay. The concept of using plasmonic heating for PCR amplification was first demonstrated in 2012 by Roche et al [120]. In their study, 60 nm citrate-capped Au NPs were added directly to the PCR reaction mixture to a final concentration of 6.6 pM ( Fig.…”
Section: Plasmonics-enhanced Polymerase Chain Reaction (Pcr)mentioning
confidence: 99%
“…More recently, plasmonics-generated localized heat, a process known as photothermal conversion, has been utilized to speed up the rate of PCR assay. The concept of using plasmonic heating for PCR amplification was first demonstrated in 2012 by Roche et al [120]. In their study, 60 nm citrate-capped Au NPs were added directly to the PCR reaction mixture to a final concentration of 6.6 pM ( Fig.…”
Section: Plasmonics-enhanced Polymerase Chain Reaction (Pcr)mentioning
confidence: 99%
“…The plasmonic amplification is carried out by photothermal heating of evenly dispersed gold nanorods (AuNRs) in PCR reaction by an 808nm vertical-cavity surface emitting laser (VCSEL) irradiation [13][14][15][16]. The real time detection is based on measuring transmitted 260nm power from a UV LED through PCR solution by a photodetector [17,18].…”
Section: Introductionmentioning
confidence: 99%
“… 12 - 14 In addition, it has been shown that gold-based materials such as GNPs and gold thin films can be used as photothermal sources to achieve rapid thermal cycling for DNA amplification upon laser irradiation. 15 - 17 However, such approaches still require a separate cell lysis step to obtain genomic DNA prior to PCR thermocycling. 18 , 19 A potential solution to this limitation is provided by recently reported cell lysis methods based on the laser-induced photothermal effect of GNPs or gold nanorods (GNRs), which is capable of lysing bacterial cells through heat shock, thereby releasing genomic DNA for subsequent conventional PCR.…”
Section: Introductionmentioning
confidence: 99%